Clinical and diagnostic features of angiosarcoma with pulmonary metastases: A retrospective observational study. Issue 36 (September 2017) - Wang, Hanping; Shi, Juhong; Liu, Hongrui; Chen, Yeye; Wang, Yining; Wang, Wenze; Zhang, Li
Abstract : Abstract: Angiosarcoma with pulmonary metastasis is a rare, fatal disease that often presents with multiple pulmonary nodules and diffuse alveolar hemorrhage. We herein review the detailed clinical characteristics of pulmonary metastatic angiosarcoma and determine a reasonable diagnostic strategy. The medical records of 11 patients with pulmonary angiosarcoma were reviewed. The mean age of the patients was 45.7 years (range, 30–71 years). All patients were male. The most common symptom was hemoptysis (8/11). Common initial misdiagnoses were tuberculosis (5/11), vasculitis (2/11), nontuberculous infectious disease (1/11), and constrictive pericarditis (1/11). Chest computed tomography (CT) of patients with hemoptysis showed bilateral, randomly distributed, variably shaped, and differently sized nodules, as well as ground-glass opacities (GGO) (8/11). The right heart was the most common primary tumor site (8/11), but the sensitivity of echocardiography was limited; CT angiography and cardiac magnetic resonance imaging (MRI) revealed more atrial masses. CT-guided needle biopsy was difficult to perform in most patients because of the small size of the nodules. The diagnosis was made by surgical biopsy of either the lung (3/9) or heart (6/9). The median overall survival of patients who underwent lung biopsy and those who underwent cardiac/pericardiac biopsy was 4.1 and 1.4 months, respectively ( P  = .098). The median overall survival of the 9 available patients was 5.0 months (95% confidence interval, 0.500–8.544). Angiosarcoma with pulmonary metastases should be considered in patients with hemoptysis and concurrent GGO and nodules on their chest CT scan. Careful cardiologic monitoring is necessary for these patients, even without any cardiac symptoms or signs, and enhanced cardiac MRI is the first recommendation. Surgical biopsy is reliable for histological diagnosis, but the safety of the lung biopsy should be carefully assessed. When primary cardiac tumors are identified, heart biopsy should be preferentially considered.